Studi Literatur Analisis Risiko Operasional Pada Perbankan Syariah - Sakti, Rafli; majdina, putri (SMARTINDO, 2024)
This research was conducted with the aim of analyzing operational risk in Islamic banking through the developed literature and reading and then drawing conclusions. Operational risk in Islamic banking aims to consider operational risks that can affect operating performance both internally and externally. By conducting this research we can review the literature on operational developments in Islamic banking.Keywords: Risk, Operational, Islamic Bank